Josef Pieper and the recovery of leisure in the workaday world - Rundell, Lauren (My University, 2022)
In this paper, I look at Josef Pieper’s conceptualization of what he calls “total work”. In the world of total work, one’s value is reduced to their practical value to society. In this world, Pieper argues that we lose our ability to realize our full humanity by limiting ourselves to only the concerns of the workaday. The missing element that Pieper brings forward is that of leisure. Leisure, Pieper explains, is a time and place in which we are able to be fully human, free from concerns of the everyday. By recovering the practice of leisure, Pieper believes we can recultivate that which makes us distinctly human and reclaim our value as more than just our output. One of the activities Pieper proposes to promote leisure, the example that I will be focusing on here, is his example of philosophy. When properly practiced, Pieper argues that philosophy can lead to the realization of one’s humanity through experiencing a deeper understanding and affirmation of the world. Through looking at Pieper’s writings on total work, leisure, and philosophy, I will argue that the University should be a space dedicated to the fulfillment of the individual by distinguishing it from concerns of the everyday. I will then argue that this should be done by grounding academic disciplines in philosophy and practicing them in a philosophical way. By reuniting the University with its foundation in philosophy, the university can be re-established as a place of leisure, where one can realize their full humanity.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta.
Keywords: total work; leisure; philosophy; Josef Pieper